DESIGN E-LEARNING SYSTEM BASED ON INFORMATION WEBSITE USING PHP AND MYSQL - Stevi Ariguna; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Along with the n ecessity of learning methods and concepts for more effective and efficient utilization of information technology for education becomes more inevitable. The concept which was then known as E- learning had an impact in the transformation process into a digital form of conventional education, both in contents (contents) and the system.  Through the existence of distance learning  E-learning is expected to get the best solutions in learning and meet the needs of society, especially students to become effective and efficient, especially in the education sector.  Based on these needs, the authors are interested in creating E - learning is a dynamic and interactive learning media as much, especially for students majoring in computer science with information systems use MySQL database. E-learning is also using PHP technology together with HTML and CSS for beautify the graphic view as well as the author uses the XAMPP web server..